L'intervista immaginata Da genere mediatico a invenzione letteraria - GALLERANI, Guido Mattia (Moderna/Comparata, 2022)
Journalism invented the interview, a tool to investigate the lives of writers. This indiscretion triggers the authors' reaction: a new literary genre, the imagined interview, becomes a shield to protect their own intimacy as wells as a tactic to overturn the press' spotlight, primarily against the interviewers. Pretending to be like them, the authors will also be able to talk to the ghosts of our imagination. All their interlocutors become characters shaped by irony, satire, self-representation. Through the creative variations of the imagined interview and across different media (publishing, radio, television, digital devices), this book shows how the media context, with its laws and conflicts, is the scene of writers' counterattack-a battle fought by the double-edged sword of journalistic imitation and fictional invention.